Primary malignant melanoma of esophagus shared similar genetic characters with both cutaneous and oral mucosal melanoma - Li, Jingjing; Yan, Shi; Wu, Nan (Journal of Thoracic Disease, 2018)
We read with interest of the letter to the editor by Dr. Krauthammer. We appreciate the author for sharing his experiences in melanoma genome research, especially his insights into different melanoma subtypes. Primary malignant melanoma of esophagus (PMME) is subtype of mucosal melanoma, just like other subtypes of mucosal melanoma, it was difficult to make sure whether it was a primary mucosal melanoma or a metastasis site which originated from a cutaneous site.